Kann Regionalplanung durch kooperative Ansätze eine Aufwertung erlangen? - Knieling, Jörg; Fürst, Dietrich; Danielzyk, Rainer (Raumforschung und Raumordnung | Spatial Research and Planning, 2001)
Co-operation has become a buzzword of our times, but it is both costly and conditioned. Based on empirical studies in Baden-Württemberg, Brandenburg, North Rhine-Westphalia and Saxony, it can be shown that regional planners run into difficulties with co-operative approaches: frequently they have to stage-manage co-operation, they are restricted in their selection to those topics which hold the prospect of win-win solutions, can muster only very few co-operands, are ill-equipped to take on the role of initiator, and more often than not are confronted with competing regional actors harnessing the regional willingness to co-operate. From the findings presented, conclusions are drawn as to how planners should improve the situation they find themselves in.
Keywords: Article